Correlation Between Hepatocyte Growth Factor Levels and Axial Length in Severe Myopic Patients - Atiyatul Amra, Aryani; Rahmawaty Lubis, Rodiah; Lelo, Aznan; Siahaan, Lambok; Sayuti, Kemala; Munir, Delfitri; Juwita Sembiring, Rosita; Mahmud Amin, Mustafa (Journal of Neonatal Surgery, 2025)
Background: Operative procedures have led to various side effects, including dry eyes, overcorrection, undercorrection, optical aberrations such as glare, ghost images, halos, and infections. Objective: To analyze changes in plasma levels of hepatocyte growth factors (HGF) levels and their effects on the progression of axial length (AL) in severe myopia. Method: This is a cross-sectional study that included all patients with severe myopia seeking treatment at USU Hospital. Results: A total of 30 patients included in this study, with a mean HGF level of 1.17 ± 0.73 ng/mL. The left eye-AL (LE-AL) averaged 26.21 ± 0.14 mm, and the right eye-AL (RE-AL) averaged 26.17 ± 0.14 mm. Significant moderate positive correlations were found between HGF levels and both LE- AL (r = 0.479, p = 0.007) and RE-AL (r = 0.414, p = 0.023). Conclusion: HGF levels are positively correlated with AL in patients with severe myopia. These suggest that HGF may play a role in the pathogenesis of axial elongation and could serve as a potential biomarker for monitoring disease progression in severe myopia.